تأثير طريقة ونوع التسميد العضوي والحيوي في بعض المؤشرات المورفولوجية والإنتاجية لدى صنف القطن 124 (Gossypium hersutum L.) - عبد العزيز, محمد; عدلة, وسيم; ابراهيم, عاصم (Latakia University Journal -Biological Sciences Series, 2018)
أجري البحث في محطة بحوث جب رملة التابعة لمركز بحوث الغاب – الهيئة العامة للبحوث العلمية الزراعية عام 2017، بهدف دراسة تأثير ثلاثة أنواع من الأسمدة العضوية والحيوية (البكتيريا Bacillus المحللة للفوسفات، وحمض الهيوميك، والأحماض الأمينية) وثلاث طرائق تسميد (نقع البذور، وسقاية النباتات، ورش المجموع الخضري) في بعض المؤشرات المورفولوجية والإنتاجية لصنف القطن 124 (Gossypium hersutum L.). طبق تصميم القطاعات العشوائية الكاملة (RCBD) بنظام القطع المنشقة لمرة واحدة Split Plot Design وبثلاثة مكررات، إذ احتل العامل الأول (نوع السماد) القطع الرئيسية، بينما احتل العامل الثاني (طريقة التسميد) القطع المنشقة، أجري التحليل الإحصائي باستخدام برنامج Genestat.12 وحسب أقل فرق معنوي L.S.D. عند مستوى المعنوية 5%. شملت المؤشرات المدروسة عند بداية مرحلة الإزهار: ارتفاع النبات، والوزن الرطب للنبات، والوزن الجاف للنبات، ومساحة المسطح الورقي، وإنتاجية النبات من القطن المحبوب. أظهرت النتائج تفوق متوسط المعاملة بالأحماض الأمينية معنوياً على باقي متوسطات المعاملات من حيث ارتفاع النبات (70.70سم)، والوزن الرطب للنبات (201.50غ)، والوزن الجاف للنبات (83.41غ)، ومساحة المسطح الورقي (4240.15سم2/نبات)، وإنتاجية النبات من القطن المحبوب (75.13غ)، كما اتضح تفوق متوسط رش المجموع الخضري معنوياً على متوسطي الطريقتين الباقيتين من حيث مختلف المؤشرات المدروسة. The research was carried out at Jeb Ramlah Research Station – AlGhab Research Center - General Authority of Scientific Agricultural Research at 2017 growing season. The objective was to investigate the effect of three organic and bio fertilizers (Bacillus, Humic acid and Amino acids) and three fertilization methods (Soaking seeds, Vegetative spraying and Plant irrigation) in some morphological and production traits of cotton cultivar 124 (Gossypium herutum L.) The experiment was conducted according to RCBD with three replications. The first factor (fertilizer type) occupied the main plots, while the second factor (fertilization method) occupied the split plots. Statistical analysis was carried out using the Genestat.12 software and the least significant difference L.S.D. at 5% level was calculated. Studied traits included (at the beginning of Blooming stage): Plant Height, Plant wet weight, Plant dry weight, Leaf area and plant production of cotton. The results showed that the average of treatment of amino acids was superiority significant on the others in terms of plant height (70.70cm), Plant wet and dry weight (201.50, and 83.41g), respectively, Leaf area (4240.15cm2/plant) and plant production of cotton (75.13g). For fertilization method, Vegetative spraying average was superiority significant on the others in terms of all studied traits.